KONDISI SOSIAL EKONOMI RUMAH TANGGA MISKIN DI KELURAHAN BINUANG KAMPUNG DALAM KECAMATAN PAUH KOTA PADANG - Mulyati, Desi; Suarto, Dedi; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This study aims to determine the socio-economic conditions of poor households in the Village Binuang In Kampung Padang Pauh subdistrict. This research is descriptive. The population in this study were all poor households in the village Binuang Kampung Padang Pauh In District totaling 44 households. Samples were taken in two ways, the sample area is taken by using purposive sampling to appoint RW1 as sample areas on the grounds of poor households more than other areas of the 20 families, while the respondent sample was taken with a total sampling technique, so the total sample of 20 families home poor. The research found that: 1) The level of education is generally poor household that completed secondary school (30.0%) and his wife graduated from junior high school level (40.0%), primary school children are studying at 35.0%, the child is taking amounted to 25.0% of secondary school education, children are studying SMA of 25.0% and was educated at the college level is 15.0%. Poor households have children who drop by 35.0% with the number of children 1-3 people. Educational facilities that can be provided by the poor households are desks, books and clothing (45.0%), (2) Work of poor households in the Village of Kampung Binuang In general, the services sector (60.0%) with an employee (60, 0). The average poor households do not have a second job (80.0%) and (3) family income of poor households are generally low at> Rp 1,000,000 - Rp 1.999.000 (100.0%), spending an average < Rp 1.500.000 - Rp 1.999.000 (85.0%). Of such income, poor households are able to meet the needs of food and clothing (65.0%). Number of dependents an average of 4 people (40.0%) and the dependents other than children and wife by 2 people (55.0%).